2006
DOI: 10.1063/1.2364155
|View full text |Cite
|
Sign up to set email alerts
|

Effect of non-Maxwellian particle trapping and dust grain charging on dust acoustic solitary waves

Abstract: The role of adiabatic trapped ions on a small but finite amplitude dust acoustic wave, including the effect of adiabatic dust charge variation, is investigated in an unmagnetized three-component dusty plasma consisting of electrons, ions and massive micron sized negatively charged dust particulates. We have assumed that electrons and ions obey (r,q) velocity distribution while the dust species is treated fluid dynamically. It is found that the dynamics of dust acoustic waves is governed by a modified r depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…[25][26][27][28] Moreover in situ rocket and satellite observations reveal that the signatures of high energy electrons ͑ϳ10 keV͒ are associated with Alfvénic electromagnetic waves. 29,30 The manuscript of the paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28] Moreover in situ rocket and satellite observations reveal that the signatures of high energy electrons ͑ϳ10 keV͒ are associated with Alfvénic electromagnetic waves. 29,30 The manuscript of the paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…[21] Using the same procedure as presented in ref. [22], we obtain the expression for the normalized electron number density as…”
Section: Basic Equationsmentioning
confidence: 99%
“…ionosphere, solar wind, interstellar medium, planetary magnetosphere, and magnetosheaths. The perpendicularly propagating electromagnetic modes in a strongly magnetized plasma were studied by Zaheer et al [21] Rubab et al [22] found that the spectral indices (r, q) modify the DAWs and affect the dust charge fluctuation. Vasyliunas was the first to introduce a mathematical function, the so-called kappa or generalized Lorentzian distribution, containing the spectral index to model the velocity distribution of high-energy electrons within the plasmas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some new models for nonthermal plasmas ͓such as ͑r , q͒ distribution͔ have been employed to study various electrostatic and electromagnetic waves and instabilities in a dusty/dust free plasmas. [29][30][31][32][33][34] Kinetic Alfvén wave ͑KAW͒ like streaming instabilities in a dusty plasma using a two-potential approach have not been investigated, when the background plasma is kappa distributed. Our aim is to fill in the gap and highlight the influence of kappa distributed ions and unmagnetized dust on the streaming instabilities.…”
Section: Introductionmentioning
confidence: 98%